Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan (Studi Kasus Di PT. Borwita Citra Prima Maumere) - Marianus Vicy Adastian; Yoseph D. Purnama Rangga; Pipiet Niken Aurelia (Jurnal Manajemen Riset Inovasi, 2023)
This research background is that customer satisfaction has not been maximized at PT. Borwita Citra Prima Maumere. This research was conducted to (1) find out how the description of service quality and promotion on customer satisfaction at PT. Borwita Citra Prima Maumere; (2) find out whether there is an influence of sevice quality and protionj on customer satisfaction at PT Borwita Citra Prima Maumere. The population in this research was all customers who currently utilized products from PT Borwita Citra Prima Maumere as many as 3178 customers. By using the Slovin formula, the sample in this study was 100 people. Data were collected by distributing questionnaires and analyzed using descriptive statistical methods and inferential statisticks, namely simple linear regression. Hypothesis testing was done through the t-test. The study’s findings demonstrated that service quality (X1) and promotion (X2) simultaneously influenced consumer satisfaction (Y) where the value of F-count > F-table, 83.486 > 3.09 then H0 was rejected. It can be concluded that both independent variables, service quality and promotion variables, had a significant influence on customer satisfaction.